Appendix 5.2: “A Man of His Time,” A Year Before Martial Law, 11 September 1971 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
This piece of propaganda was published in the first (and only?) issue of  The Leader , which focused on Ferdinand Marcos’s fifty-fourth birthday. That birthday came mere weeks after the bloody Plaza Miranda bombing and Marcos’s suspension of the privilege of the writ of habeas corpus on 21 August 1971. Marcos here is portrayed as a liberal, though one willing to use force when necessary in response to the “new radicalism” of the time; a freedom/national security paradox is mentioned, but the only resolution offered thereto is trust in the leadership of the president. Marcos, portrayed as far superior to his immediate predecessors (Carlos Garcia and Diosdado Macapagal), is doing precisely what is necessary, readers are being told, a little over a year before the declaration of martial law.